ADVANCEMENTS IN DIAGNOSIS AND TREATMENT METHODS FOR POOR-QUALITY TUMORS AND PULMONARY TUBERCULOSIS IN CASES OF COMORBIDITY - Isomiddin H. Usmanov; Iroda M. Iskandarova (Central Asian Journal of Medicine, 2024)
This study focuses on enhancing diagnostic and therapeutic approaches for individuals suffering from both poor-quality tumors and pulmonary tuberculosis concurrently, a challenging medical scenario. Key objectives include refining diagnostic accuracy, optimizing treatment efficacy, and improving patient outcomes. Through a comprehensive literature review and analysis, this research aims to address the complexities of comorbid conditions, offering insights into innovative methodologies and strategies. Material and methods involve a systematic review of relevant studies, clinical data analysis, and computational modeling. Results showcase promising advancements in imaging techniques, molecular diagnostics, targeted therapies, and multidrug regimens tailored for comorbid patients. Conclusion emphasizes the importance of interdisciplinary collaboration, personalized medicine approaches, and ongoing research efforts to effectively manage this intricate medical condition.